Ultrasonographic assessment of lower limb muscle architecture in children with early-stage Duchenne muscular dystrophy - BULUT, Numan; KARADUMAN, Ayşe; ALEMDAROĞLU-GÜRBÜZ, İpek; YILMAZ, Öznur; TOPALOĞLU, Haluk; ÖZÇAKAR, Levent (Arquivos de Neuro-Psiquiatria, 2022)
Background: Muscle imaging methods such as ultrasound and magnetic resonance imaging have been used for many years to determine the dystrophic process in muscular dystrophies. However, the knowledge regarding muscle architecture in children at early-stage Duchenne muscular dystrophy (DMD) with different functional levels is limited. Objective: To explore the effect of functional level on muscle architectural properties in children with early stage DMD and the difference between DMD and typically developing (TD) peers. Methods: Thirty children with DMD (15 Grade 1 and 15 Grade 2 according to the Vignos Scale) and 5 TD peers were included. Ultrasound imaging was used to measure muscle thickness (MT), fascicle length (FL), and pennation angle (PA) of vastus lateralis (VL) and medial gastrocnemius (MG) muscles bilaterally. Results: The MT and FL values for VL, and MT, FL and PA values for MG muscles were higher in children with DMD compared with those of TD peers (p<0.05). The FL of VL, and MT and FL of GM muscles of children with DMD Grade 2 were higher than those of children with DMD Grade 1 (p<0.05). Conclusions: MT and FL are increased in children with DMD compared with TD peers. Additionally, muscle architecture seems to be affected even at the early stages of the disease.
Keywords: Muscles; Ultrasonography; Muscular Dystrophies; Architecture; Physical Functional Performance